2011
DOI: 10.1016/j.compscitech.2011.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Internal stresses and voids in SiC particle reinforced aluminum composites for heat sink applications

Abstract: Please cite this article as: Schöbel, M., Altendorfer, W., Degischer, H.P., Vaucher, S., Buslaps, T., Di Michiel, M., Hofmann, M., Internal stresses and voids in SiC particle reinforced aluminum composites for heat sink applications, Composites Science and Technology (2011), doi: 10.1016/j.compscitech.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…[5][6][7]. For example, SiC p reinforced AMCs are used for engine piston, and heat sink [8,9]. Compared with traditional micron-sized SiC p /Al composites, the higher tensile strength and good ductility of the nano-sized SiC p /Al composites entitle them to have more competitive ability for advanced structural applications such as in automotive and aerospace industries and the military [10].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]. For example, SiC p reinforced AMCs are used for engine piston, and heat sink [8,9]. Compared with traditional micron-sized SiC p /Al composites, the higher tensile strength and good ductility of the nano-sized SiC p /Al composites entitle them to have more competitive ability for advanced structural applications such as in automotive and aerospace industries and the military [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tensile damage behavior of SiC particle reinforced aluminum alloy matrix has been studied using in situ X-ray synchrotron tomography [30]. In situ X-ray synchrotron tomography has been used for 3D observation and quantification of fatigue cracking in Al-Mg-Si alloys [31] and to visualize void volume changes due to thermal fatigue damage in SiC particle reinforced aluminum [32].…”
Section: Introductionmentioning
confidence: 99%
“…The gauge volume in the sample is defined by primary and secondary slits. An angle dispersive diffraction measurement on an AlSi7/SiC/70p PRM (Schöbel et al, 2011) is shown in Fig. 5.…”
Section: Angle Dispersive Neutron Diffractionmentioning
confidence: 99%
“…12. In situ neutron stress measurement during thermal cycling of AlSi7/SiC/60p (RT -350°C) showing the stress changes in the -Al and in the particle stresses (Schöbel et al 2011). …”
Section: Neutron Diffraction 274mentioning
confidence: 99%
See 1 more Smart Citation